THE IMPACT OF OWNERSHIP STRUCTURE AND CAPITAL STRUCTURE ON FIRM’S VALUE - Silvi Delfiani; Mohamad Fany Alfarisi (LPPM Universitas Ekasakti, 2021)
The objective of the present study is to investigate the impact of insider ownership, institutional ownership and capital structure on firm’s value. The population of this study is all manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in the period of 2011-2016. We use panel data regression with 174 observations. For hypothesis testing, the present study employs the t-test with ? 10% level of significance. The results suggest that institutional ownership and firm size have significant impact on firm’s value